PENGUJIAN HAMBATAN HUBUNGAN MENTORING DAN KEINGINAN BERPINDAH PADA AKUNTAN PUBLIK - Murtini, Henny (Universitas Muhammadiyah Magelang, 2006)
The research amis at identifying and examining of perceived barriers to mentoring and turnover intentions in public accounting. Hypotheses developed from this framework are tested based on a sample of 90 public accounting from local, intermediate, and big CPA firm in Indonesian. The instruments for collecting the data are questioners. Accordingly, this research purpose also is to provide evidence on perceived barriers to forming mentoring and peer relatonship in public accounting. Analysis of responses indicated six interpretable factors representing barriers to forming mentoring relationship. The research finding show that first, participants with a mentor perceived lower barriers from access to mentor. Second, gender differences were significant only from willingness of mentor. Third, lower-ranked public accounting perceive greater barriers to mentoring relationship than higher-ranked public accounting from approval of others and willingness of mentor. Fourth, when public accounting firm size is different, perceived barriers to mentoring relationship will be different but only willingness mentor. Finally, public accounting without turnover intentions lower barriers from approval of other.